Structural design and analysis amphibious boat / Izzul Faiz Farhan Mohd Utama - Mohd Utama, Izzul Faiz Farhan (2022)
This projects' objectives are to design and analyse the frame of structure of the Amphibious Boat. Amphibious boat is a type of boat that have 2 functions, which is to be use on water surface and on land. In this project, the material that will be use are GRP(Glass Reinforced Plastic). The basis analysis of this project is the mechanical properties of the material used such as yield strength, ultimate strength, compressive strength, elongation characteristics and plastic deformation, fracture, and fatigue characteristics. Since Amphibious boat will be use on water and on land, so there were a several problems which is to create the frame structure of the boat based on selected hull design based on the ABS Rule and classification as requirement for safeguard and safety.